2013
DOI: 10.5194/amt-6-63-2013
|View full text |Cite
|
Sign up to set email alerts
|

Profiling tropospheric CO<sub>2</sub> using Aura TES and TCCON instruments

Abstract: Abstract.Monitoring the global distribution and long-term variations of CO 2 sources and sinks is required for characterizing the global carbon budget. Total column measurements are useful for estimating regional-scale fluxes; however, model transport remains a significant error source, particularly for quantifying local sources and sinks. To improve the capability of estimating regional fluxes, we estimate lower tropospheric CO 2 concentrations from groundbased near-infrared (NIR) measurements with space-base… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 66 publications
(77 reference statements)
1
18
0
Order By: Relevance
“…2. Even though little information seems to be added by using the full profile, 3-D var assimilation of TES profiles (described in Kuai et al, 2013) compared better to validation data than a single level assimilation (unpublished work).…”
Section: Characterizing Sensitivity Through Assimilationmentioning
confidence: 99%
“…2. Even though little information seems to be added by using the full profile, 3-D var assimilation of TES profiles (described in Kuai et al, 2013) compared better to validation data than a single level assimilation (unpublished work).…”
Section: Characterizing Sensitivity Through Assimilationmentioning
confidence: 99%
“…M. Worden et al, 2010;Kuai et al, 2013). In the case where the trace gas varies significantly in the free troposphere, it is necessary to estimate the trace gas profile from the radiances when the reflected sunlight and thermal IR measurement observe the same air parcel (e.g., H. M. Worden et al, 2010).…”
Section: Estimating Lower-tropospheric Methane From Gosat and Tesmentioning
confidence: 99%
“…In the case where the trace gas varies significantly in the free troposphere, it is necessary to estimate the trace gas profile from the radiances when the reflected sunlight and thermal IR measurement observe the same air parcel (e.g., H. M. Worden et al, 2010). For long- lived trace gases such as CO 2 (e.g., Kuai et al, 2013) we can subtract the free-tropospheric/stratospheric posterior estimate (based on thermal IR radiances) from the total column (based on reflected sunlight radiances). In this case observations that are not exactly co-located in space and time can be used together to estimate lower-tropospheric concentrations because of the long mixing length scales of these trace gases in the free troposphere and stratosphere (Sect.…”
Section: Estimating Lower-tropospheric Methane From Gosat and Tesmentioning
confidence: 99%
“…In this paper we evaluate the calculated uncertainties due to noise and interferences in the OCO-2 data product (version 7). Our approach follows the methodology described in Boxe et al (2010) and Kuai et al (2013) in which variations of the observed trace gas over a small "area" are compared to the calculated errors.…”
Section: Introductionmentioning
confidence: 99%